Draft Genome Sequence of Heavy Metal-Resistant Aeromonas Veronii Cte-01, Isolated from a Peruvian Wastewater Treatment Plant - Vasquez-Guzman, C (American Society for Microbiology, 2019)
Here, we report a draft genome sequence of Aeromonas veronii strain CTe-01 (4.5 Mb), a hemolytic, heavy metal-resistant bacterium isolated from a wastewater treatment plant located at Cachiche, Ica, Peru. These characteristics could be used for bioremediation of contaminated environments. Copyright © 2019 Tataje-Lavanda et al.